Konstruksi Kesalehan Simbolik Dalam Gaya Hidup Islami di Media Sosial: Studi Netnografi Akun Instagram @diary.islami dan @halalcorner - Rina Darojatun (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2022)
This article will describe the virtual Muslim audience who constructs themselves to appear pious with the symbols attached to them and can spread their piety through social media, because the choice of an Islamic lifestyle cannot be separated from the symbols of Islam attached to it. The symbolic piety that emerged made middle class Muslims have different characteristics and religious principles. This article analyzes the interactions on the Instagram accounts @diary.islami and @halalcorner, using the netnographic method to deeply understand the life of the virtual community from the perspective of the perpetrator. The results of the study show that the hijab can be a strategy to show the image of symbolic piety wrapped in hijrah in four levels of easy, normal, hard and expert, the prohibition of growing eyelashes does not stop Muslim women from beautifying themselves, and the fever of K-pop as popular culture influences mass culture. in the form of consumption of Korean food products and other imported products to be tested for halal by BPOM and MUI, this is used to attract the majority segment of Muslim fans.